PURIFICATION AND SOME PARTIAL CHARACTERIZATION OF PEROXIDASE ISOENZYME FROM BRASSICA OLERACEA CAPITATA L. (Journal of Sciences, Islamic Republic of Iran)
Acetone fractionated peroxidase from crude extract of Brassica oleracea leaves (Cabbage) was purified in three steps on chromatographic columns, using Sp-Sepharose, DEAE-Sepharose and Con A-Sepharose. The specific activity of purified main isoenzyme (BOC-POD) is 1887 u/mg protein with RZ: 3.1, which is 172 times more than the RZ of crude extract with 4.3% recovery. The molecular weight of BOC-POD is about 45,000 Dalton. Maximum pH, thermal activity and stability of this purified enzyme are also determined. Km of this isoenzyme was measured by Linewearver-Burk curve for O-dianisidine towards H2O2. This purified enzyme could be used in manufacturing diagnostic kits.